Action at a Distance in Arginine Repressor and the Store-operated Calcium Channel Orai: Molecular Modeling and Simulations - Pandey, Saurabh Kumar (Jihočeská univerzita, 2018)
In this thesis molecular modeling tools have been applied to investigate the phenomenon of allostery in two systems: Arginine repressor and human Orai channel. Arginine repressor protein binds to DNA in response to the intracellular concentration of L-arginine and controls the arginine metabolism in bacteria. Using molecular dynamics simulations sampling of the conformational space of arginine repressor and the allosteric effects of L- arginine binding on structure and dynamics of systems were studied. Orai channels are responsible for entry of calcium ion in the cell in response to Ca 2+ depletion in the endoplasmic reticulum. Homology modeling was applied to prepare a structural model of human Orai3. Molecular dynamics simulations of the earlier published Orai1 model and the Orai3 model described here were performed. Results pointed to differences in the structures and dynamics of the two Orai isoforms, Orai1 and Orai3 and consequent effects on the channel which are probably responsible for the different behavior of Orai isoforms. A putative cholesterol binding site was identified using in silico docking approach and possible effects of cholesterol binding on the Orai1 channel structure and function were reported. Allosteric effects of mutations on a distant cholesterol- binding pocket was investigated.
Action at a Distance in Arginine Repressor and the Store-operated Calcium Channel Orai: Molecular Modeling and Simulations
Keywords: Molecular dynamics simulation; Allostery; Arginine repressor; Orai Channel; Molecular dynamics simulation; Allostery; Arginine repressor; Orai Channel